Effect of ecoliteracy on farmers’ participation in pesticide packaging waste governance behavior in rural North China - Yang Song; Haixia Cui; Yixiang Zong; Shi Yin (Scientific Reports)
Abstract Farmers’ participation in pesticide packaging waste (PPW) governance is important for improving agricultural pollution and achieving sustainable agricultural development. By incorporating the theory of planned behavior, value-belief-norm theory, cognition and behavior theory etc., we construct a theoretical model comprising “ecoliteracy–farmers’ WTP in PPW governance–participation in PPW governance behavior.” This study investigates how ecoliteracy affects farmers’ participation in PPW governance and explores the mediating effect of farmers’ willingness to participate (WTP) in PPW governance. We use structural equation modeling to analyze data collected from a questionnaire survey including 1118 samples of Chinese farmers. The results show that (1) Ecoliteracy significantly affects farmers’ WTP in PPW governance. Ecological cognition, emotion, values, and knowledge and skills positively affect WTP in PPW governance, while ecological cognition and ecological knowledge and skills significantly affect participation in PPW governance behavior. (2) Farmers’ WTP in PPW governance mediates ecoliteracy and governance participation behavior. (3) Heterogeneity analysis reveals that different planting scales, different planting categories, and receiving/not receiving government project support have different effects on farmers’ participation in governance behavior. Farmers in the large-scale group are more likely to participate in governance than those in the medium- and small-scale groups, and farmers in the mixed grain and economic category are more likely to participate in governance than those in the economic and grain categories. Furthermore, farmers who receive government support are more likely to participate in governance than those who do not. Our results can serve as a policy making reference for promoting PPW governance in various regions.